2014
DOI: 10.1001/jama.2014.7860
|View full text |Cite
|
Sign up to set email alerts
|

Brief Intervention for Problem Drug Use in Safety-Net Primary Care Settings

Abstract: IMPORTANCE Although brief intervention is effective for reducing problem alcohol use, few data exist on its effectiveness for reducing problem drug use, a common issue in disadvantaged populations seeking care in safety-net medical settings (hospitals and community health clinics serving low-income patients with limited or no insurance). OBJECTIVE To determine whether brief intervention improves drug use outcomes compared with enhanced care as usual. DESIGN, SETTING, AND PARTICIPANTS A randomized clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
166
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 180 publications
(181 citation statements)
references
References 41 publications
(49 reference statements)
13
166
0
2
Order By: Relevance
“…Saitz et al [36] tested the efficacy of a brief negotiated intervention for any illicit drug use or prescription drug misuse versus no BI, and found no effect. Roy-Byrne et al [37] found no effect of a BI plus telephone booster for drug use. These two studies emphasize the need for deliberate, targeted use of SBIRT public health rather than as a panacea.…”
Section: Discussionmentioning
confidence: 98%
“…Saitz et al [36] tested the efficacy of a brief negotiated intervention for any illicit drug use or prescription drug misuse versus no BI, and found no effect. Roy-Byrne et al [37] found no effect of a BI plus telephone booster for drug use. These two studies emphasize the need for deliberate, targeted use of SBIRT public health rather than as a panacea.…”
Section: Discussionmentioning
confidence: 98%
“…However, even this low dose is comparable to studies with more intense interventions, and this amount of exposure yielded more overall clinical benefit than has been seen in some trials consisting of only a single brief intervention. 49 A potential explanation for the improvement in PTSD diagnosis and severity score at 6 months is regression to the mean. That is, patients were enrolled on the basis of initial high PTSD severity scores.…”
Section: Discussionmentioning
confidence: 99%
“…This issue has particular importance in light of the recently published studies that demonstrated lack of efficacy of brief intervention for unhealthy drug use in primary care. 7,15 The purpose of this study is to describe the prevalence of chronic pain and pain-related dysfunction among primary care patients who screen positive for drug use. In addition, we examine the prevalence of alcohol and illicit drug use and prescription drug misuse for the purpose of self-medicating chronic pain in this population.…”
Section: Introductionmentioning
confidence: 99%